Análise dos gols em jogos de futsal feminino de alto rendimento - Santana, W. C.; Laudari, B. A.; Istchuk, L. L.; Arruda, F. M. (Revista Brasileira de Ciência e Movimento, 2013)
The purpose of the study was to analyze female futsal goals during official matches. We selected four observational indicators: (1) goal origin, i.e., attacking type; (2) ball distance from the goal (short, medium, long and very long); (3) court location (center, right and left wing) and (4) goal period (1st, 2nd, 3rd, 4th). The study was observational descriptive of a transversal design. We analyzed 90 goals (6 ± 2.95 goals per match) during 15 matches of the Finals of the XVIII Taça Brasil de Clubes Championship. Results showed that the great part of the goals came from positional attack, followed by counter-attack and from restarting plays (i.e., corner kick, free kick, etc). An expressive lower number of goals came from other situations, such as, attacking with the goalkeeper. The results also showed that the great part of the goals was performed from the center of the court, in a short distance, followed by a medium distance from the goal, and in the end of each period, i.e., in the 2nd and 4th period of the match, respectively. Our findings allowed concluding that female futsal coaches should pay attention to the defensive actions, which were deficient, especially against positional attack that, in theory, facilitates the defensive actions. On the other hand, attacking plays with the action of the goalkeeper should be improved.